The Use of Low Ammonia Concentration in the Radiochemical Purity Test of [153Sm]Sm-EDTMP by Using the Thin Layer Chromatography Method - Amal Rezka Putra; Khoirunnisa Fauziah Asyikin; Robertus Dwi Hendarto; Agus Ariyanto; Enny Lestari; Sumandi Juliyanto; Ahsanal Fikri (The Journal of Pure and Applied Chemistry Research, 2021)
Radiochemical purity testing of [153Sm]Sm-EDTMP usually uses the Thin Layer Chromatography method. The mobile phase used is a mixture of 25% ammonia and water. However, the lowest ratio of 25% ammonia in the mobile phase is unknown. Therefore, research related to the use of the lowest concentration in the radiochemical purity test of [153Sm]Sm-EDTMP is necessary. This research method includes labelling of EDTMP using Samarium-153, preparation of the mobile phase with variations in the concentration of 25% ammonia: water, radiochemical purity test and data analysis using t-test statistics. The results of this study are the concentration of 25% ammonia: water (1: 9) to (1: 200) still shows good separation with Rf of [153Sm]SmCl3 and [153Sm]Sm-EDTMP at 0.0, 1.0 respectively, whereas with a thinner concentration of ammonia indicates less optimal separation with Rf [153Sm]SmCl3 at 0.35 to 1.0. Comparison of concentrated ammonia concentrations of 1: 9 and dilute 1: 200 was performed using a statistical t-test. The results of the data analysis showed that the two methods were not significantly different, indicated by the t-value of 0.82 less than 2.78. The conclusion of this study is that the lowest concentration of 25% ammonia and water in the radiochemical purity test of [153Sm]Sm-EDTMP is 1: 200.